2006
DOI: 10.1152/ajpregu.00612.2005
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic receptors in human placenta: evidence for functionally active P2X4, P2X7, P2Y2, and P2Y6

Abstract: Appropriate regulation of ion transport by the human placental syncytiotrophoblast is important for fetal growth throughout pregnancy. In nonplacental tissues, ion transport can be modulated by extracellular nucleotides that raise intracellular calcium ([Ca2+]i) via activation of purinergic receptors. We tested the hypothesis that purinergic receptors are expressed by human placental cytotrophoblast cells and that their activation by extracellular nucleotides modulates ion (K+) efflux and [Ca2+]i. P2X/P2Y rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 52 publications
2
26
0
1
Order By: Relevance
“…Both subtypes of purinergic receptors have widespread tissue expression, including the placenta (see Tables S2 and S3). 5,24,25 …”
Section: Atp and Adenosinementioning
confidence: 99%
“…Both subtypes of purinergic receptors have widespread tissue expression, including the placenta (see Tables S2 and S3). 5,24,25 …”
Section: Atp and Adenosinementioning
confidence: 99%
“…In a study of P2 receptor mRNA and protein expression in human placental villus fragments at two stages of gestation, the first trimester and term [342], P2X4, P2X7 and P2Y 2 (but not P2Y 4 ) receptor subtypes were found and fluorescent calcium imaging experiments showed that ATP, UTP and 2′(3′)-O -(4-benzoylbenzoyl)adenosine 5′-triphosphate caused significant elevation of [Ca 2+ ] i in term compared to the first trimester. Systematic pharmacological studies of purinergic signalling in human placenta showed functionally active P2X4, P2X7, P2Y 2 and P2Y 6 receptors on cytotrophoblast cells and it was proposed that activation of these receptors and subsequent elevation of [Ca 2+ ] i modulates syncytiotrophoblast homeostasis and maternofoetal ion exchange [341]. P2Y 1 and P2Y 2 receptors are unevenly distributed along the human placental vascular tree; there is a 6-to 8-fold increase in these receptors from the cord to the chorionic or cotyledon vessels [69].…”
Section: Placentamentioning
confidence: 99%
“…Since the human placenta is not innervated, autoc r i n e , p a r a c r i n e a n d e n d o c r i n e m o d u l a t i o n o f syncytiotrophoblast transport function is of pivotal importance. Functionally active P2X4, P2X7 , P2Y 2 and P2Y 6 receptors have been identified on human placental syncytiotrophoblast cells [446]. This group showed later that post-translational modifications of the syncytiotrophoblast P2X4 receptor are altered in preeclampsia [447].…”
Section: Placentamentioning
confidence: 98%